Input use, cost structure and return analysis of Sugarcane crop in South Gujarat - Parmar, VN; Patel, KS; Pandya, CD (Journal of Agricultural Extension Management, 2019)
This paper attempts to measure the economics of sugarcane production in South Gujarat. The study was conducted during the year 2013-14 with 240 farmers. The decision and choice of crops to be grown on a farm and the area to be allocated under a crop depends to a large extent on the price of output, productivity level, technology available and the level and prices of inputs used in their production. The knowledge of input use, cost structure and returns from the cultivation of crops helps in formulating policies at macro and micro levels. Such knowledge is more useful for crops cultivated mainly for the market viz, the cash crops, spice crops, fruits, vegetables and other high value crops. This paper focuses on pattern of input use in cultivation of sugarcane crop and cost structure and returns from sugarcane cultivation. Findings of the study revealed that due to statutory price for sugarcane, this crop is grown not by choice but due to its assured returns. Moreover, due to set package of practices, the cost and returns across the farm categories did not vary much.